Flexural Buckling Resistance of Stiffeners Reinforcing Wall of a Steel Silo - Marcinowski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Stiffeners reinforcing silo`s wall made from corrugated sheets are main structural elements sustaining meridional forces evoked by shear forces, source of which is friction of the material stored inside silo. Buckling resistance of stiffeners can be assessed by the method recommended in PN-EN 1993-4-1:2009/A1-2017-08E and in the draft of the Eurocode prEN 1993-4-1:2022.
Keywords: steel silo; corrugated sheeting wall; stiffeners; buckling resistance; equivalent wall stiffness